What adaptation to research is needed following crises: a comparative, qualitative study of the health workforce in Sierra Leone and Nepal - Joanna Raven; Sushil Baral; Haja Wurie; Sophie Witter; Mohamed Samai; Pravin Paudel; Hom Nath Subedi; Tim Martineau; Helen Elsey; Sally Theobald (Health Research Policy and Systems, 2018)
Abstract Background Health workers are critical to the performance of health systems; yet, evidence about their coping strategies and support needs during and post crisis is lacking. There is very limited discussion about how research teams should respond when unexpected crises occur during on-going research. This paper critically presents the approaches and findings of two health systems research projects that explored and evaluated health worker performance and were adapted during crises, and provides lessons learnt on re-orientating research when the unexpected occurs. Methods Health systems research was adapted post crisis to assess health workers’ experiences and coping strategies. Qualitative in-depth interviews were conducted with 14 health workers in a heavily affected earthquake district in Nepal and 25 frontline health workers in four districts in Ebola-affected Sierra Leone. All data were transcribed and analysed using the framework approach, which included developing coding frameworks for each study, applying the frameworks, developing charts and describing the themes. A second layer of analysis included analysis across the two contexts, whereas a third layer involved the research teams reflecting on the approaches used to adapt the research during these crises and what was learned as individuals and research teams. Results In Sierra Leone, health workers were heavily stigmatised by the epidemic, leading to a breakdown of trust. Coping strategies included finding renewed purpose in continuing to serve their community, peer and family support (in some cases), and religion. In Nepal, individual determination, a sense of responsibility to the community and professional duty compelled staff to stay or return to their workplace. The research teams had trusting relationships with policy-makers and practitioners, which brought credibility and legitimacy to the change of research direction as well as the relationships to maximise the opportunity for findings to inform practice. Conclusions In both contexts, health workers demonstrated considerable resilience in continuing to provide services despite limited support. Embedded researchers and institutions are arguably best placed to navigate emerging ethical and social justice challenges and are strategically positioned to support the co-production of knowledge and ensure research findings have impact.